2015
DOI: 10.1007/s13762-015-0754-9
|View full text |Cite
|
Sign up to set email alerts
|

Potentially toxic elements and persistent organic pollutants in water and fish at Shahid Rajaei Dam, north of Iran

Abstract: The purpose of this study was to assess selected potentially toxic elements and persistent organic pollutants concentrations in the Shahid Rajaei Dam reservoir as well as their accumulation in barbel and Leuciscus cephalus fish species. The concentration of arsenic, mercury, nickel, chromium and cadmium in all water samples is less than WHO drinking water standard. Chromium shows a higher concentration than WHO standard in both fish species, while nickel and mercury content in barbel fish is higher than WHO st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
2
12
1
Order By: Relevance
“…The mean concentrations of DDTs, lindane and dieldrin are shown in Tables 1-3. OCPs: DDT concentration in this study is in line with observation for Karun River (36 ng/L) [44], Lake Parishan (35.5 ng/L) [45] and Lake Tashk (51 ng/L) [46] but lower than Anzali wetland (108.83 ng/L) [47] and Shahid Rajaei Dam (<LOQ to 100 ng/L) [48] in Iran. Compared with OCP levels in other rivers across the globe, the mean concentration of DDT was lower than the Hooghly River (838 ng/L) [49], River Nile (210 ng/L) [50], Pearl River Estuary (143 ng/L) [51] and Iberian Peninsula (164.93 ng/L) [52] but were higher than Moscow River (<LOQ) [53], Yongding River (4.65 ng/L) [54], Chenab River (9.07 ng/L) [55], Ravi River (12.15 ng/L) [56,57] and surface water around Bejing (0.375 ng/L) [58].…”
Section: Levels Of Selected Legacy Pops and Comparison With Other Stusupporting
confidence: 91%
“…The mean concentrations of DDTs, lindane and dieldrin are shown in Tables 1-3. OCPs: DDT concentration in this study is in line with observation for Karun River (36 ng/L) [44], Lake Parishan (35.5 ng/L) [45] and Lake Tashk (51 ng/L) [46] but lower than Anzali wetland (108.83 ng/L) [47] and Shahid Rajaei Dam (<LOQ to 100 ng/L) [48] in Iran. Compared with OCP levels in other rivers across the globe, the mean concentration of DDT was lower than the Hooghly River (838 ng/L) [49], River Nile (210 ng/L) [50], Pearl River Estuary (143 ng/L) [51] and Iberian Peninsula (164.93 ng/L) [52] but were higher than Moscow River (<LOQ) [53], Yongding River (4.65 ng/L) [54], Chenab River (9.07 ng/L) [55], Ravi River (12.15 ng/L) [56,57] and surface water around Bejing (0.375 ng/L) [58].…”
Section: Levels Of Selected Legacy Pops and Comparison With Other Stusupporting
confidence: 91%
“…The average Cr concentrations for grass carp, silver carp and mrigel were 15.10, 14.57 and 14.94 µg g -1 , respectively (Table 3). According to Shakeri et al [38], WHO set the maximum allowable concentration of Cr 0.15 µg g -1 for human. The present study results revealed that all species and sizes of fish samples contained higher amount of Cr than this limit of WHO.…”
Section: Cadmium (Cd)mentioning
confidence: 99%
“…Additionally, these problems have featured hugely in scientific publications and warnings (Tolba and Saab 2009). Such problems that have been hugely addressed in the literature include, as an examples, air pollution (Ahmadi et al 2015;Li et al 2016a), climatic changes (Carleton and Hsiang 2016; Deutsch et al 2015), industrial effluents (Padmanaban et al 2016), desertification (Juřička et al 2016;Li et al 2016b), vulnerability of groundwater to external pollutants (Damak et al 2016;Iqbal et al 2014), land degradation (Akhtar-Schuster et al 2016;Kosmas et al 2016) and aquatic environment pollution with organic and inorganic pollutants (Shakeri et al 2015).…”
Section: Introductionmentioning
confidence: 99%